Pathways to Financial Success: An Empirical Examination of Perceived Financial Well-Being Based on Financial Coping Behaviors - Shi, Junguo; Ullah, Saif; Zhu, Xun; Dou, Shanshan; Siddiqui, Faiza (Frontiers in Psychology, 2021)
The current study empirically tests a financial well-being model (FWB) built on financial socialization (FS) and early childhood experience (ECCE). The current study was conducted based on primary data obtained through structured questionnaires. By using a convenient sampling technique, data was collected from 1500 respondents from Pakistan. The results of the present study advocated that childhood experiences directly affect the FWB in adults. Additionally, FS agents such as parents have a direct and indirect effect on the FWB in adults. The findings revealed that financial coping behaviours mediate the relationship between FS agents, such as parents, students, and the FWB. Surprisingly, FS agent peers do not impact adult FWBs. It is concluded that FWB could be improved by socializing with parents and teachers and using childhood experiences. Considering the importance of the role of parents and teachers, they should discuss financial issues with children. Policymakers should work to provide some opportunities for children so that they can practice and gain experience.